Preservation of Lemuru (Sardinella lemuru) by Salting and Drying Methods at Istana Muncar Ikan SMEs of Banyuwangi District - Nandya Fitri Rachmawati (Journal of Aquaculture Development and Environment, 2022)
Lemuru (Sardinella lemuru)is the most catches in Banyuwangi. This fish called pelagic fish that swim on the surface of the sea. The abundance of lemuru catch makes this fish have a role and benefit for the society. However, fish is also quickly to spoil after harvesting. Without the preservation process, the fish is only suitable for consumption within a day after being caught. Various preservation methods have been carried out, one of which is salting and drying aimed to reduce the moisture content in the fish body, so that didn’t give chance for microorganism to breed and didn’t affect the fish quality. This study was used descriptive method with data collection techniques through primary data and secondary data. Data collection carried out with observation, interview, active participation and literature study. Research result in Istana Muncar Ikan Banyuwangi SMEs included raw material used in food processing in SMEs was lemuru (Sardinella lemuru) obtained from Muncar Port. The fish was treated with brining method by soaking fish of dilute salt solution of 30-35% from total weight of fish. After brining, drying process was carried out under the sun for 1 day and dried salted fish produced, has distinctive smell, salty taste, normal colour, also good shape. Salt content of 13-17% by weight of salted dried fish.